Currículo em ação nos anos iniciais do ensino fundamental e a atenção à multiculturalidade - Corsi, Adriana Maria (2007)
The present study had as objective identifies aspects of the pedagogic practice that can contribute to the regulation and social emancipation, discussing them starting from the studies of Critique Multiculturalism. This way, we tried to understand how the relative differences of categories race/ethnic, social class and gender are present in curriculum in action. The data were collected from two classrooms of the first grade of Fundamental Teaching - 1st and 4th series - through observation and interview. They had been accomplished thirty days of observation in each classroom, distributed for each school semester. The interviews were made with the objective of understanding the meanings attributed by the teachers to their practices. The choice of the 1st series was random and to 4th series was chosen because the teacher realized a differentiated pedagogic practice, concerned with subjects regarding the cultural diversity. The analyses point two types of quite different practices, and in the 1st series the linked aspects of differences were registered stronger in the relationships between teacher and students and in 4th series the work with the contents that he/she appears as central. In teacher Roberta's 1st series, the analyzed situations show the existence of ethnocentric pattern that rules his/her pedagogic work, mainly in what he/she refers to the relationship between her and the students, involving the attention given to certain students, the expectations positive or negative to them, the incentive, the knowledge conception and others. This aspect illustrates how inside of a same classroom they feel different teaching forms and learning and how those processes are influenced for cultural and social differences. In the 4th series teacher's Silvia, themes like prejudice, racism, stereotypes are treated together with the curricular contents. The observed situations reveal that the teacher tries to develop with the students a critical vision of different themes that involve social and cultural subjects, with an education that illustrate more the social emancipation. However, that attempt of developing a practice returned to the work with the differences is set also by some difficulties, as the isolation in the school and the domain of curricular contents in their relationships with the gender subjects, sexuality, race/ethnic. Finally, we considered that the culture is always present in the school education, as monoculturalism or multiculturalism. Therefore it is indispensable that the courses of initial and continuous formation involve the discussions of the cultural and social differences in their programs, with the objective of developing a critical education, "politics" that seeks the overcoming of the social exclusion, of the prejudice and of the racism